Čebele Slovenije - Gogala, Andrej (ZRC SAZU, Založba ZRC, 2014)
The book presents the taxonomy and systematics of bees (Anthophila) and their biology: the collection and transport of food, picky behavior of bees, which are linked to certain food plants, nesting methods, Cuckoo bees laying eggs in the nests of other species, behaviors and adaptations of males. In the chapter on the diversity of wild bees changes in the Slovenian fauna are described. In the author's opinion, they are mainly due to climate change and extreme weather conditions. The greater part of the book deals with the social life of bees, especially the primeval social forms that facilitate the understanding of the development of social communities. In the chapter Highways and byways of evolution author describes the long-term advantage of species with social or symbiotic connections over the species in which the dominance of the strongest and largest specimens in mutual combat increases the size of the specimens and reduces their number. He continues with a chapter on the various forms of social communities, with examples in bees. In the last chapter the families and genera of bees living in Slovenia are presented. Great value of the book are also 154 original photos of different species of bees, which illustrate their behavior in the wild.